UNDERSTANDING THE PROSPERITY GOSPEL. - Stephens, Randall J. (Fides et historia, 2015)
The article comments on Kate Bowler's book "Blessed: A History of the American Prosperity Gospel," which analyzes the religious culture and practice of American Prosperity. Topics discussed include Bowler's argument of prosperity gospel as a decisive theological, economic and social force in American religion and the spread of prosperity message from television (TV) and radio across the U.S.